Rupture Characteristics Analysis of the 2020 Mw 7.4 Oaxaca, Mexico Earthquake Using Teleseismic, High-Rate GPS, and InSAR Data - Wen, Guisen; Li, Xingxing; Zhao, Yingwen; Xu, Caijun; Xu, Guangyu (Frontiers in Earth Science, 2022)
The 23 June 2020 Oaxaca Mw 7.4 interplate thrust earthquake struck the state of Oaxaca in Mexico, generating strong shaking and a long-lived tsunami. This earthquake is well recorded by teleseismic, high-rate Global Positioning System (GPS) and Interferometric Synthetic Aperture Radar (InSAR) data, which provides an opportunity to understand the rupture characteristics of the Mexican subduction zone. Here an integrated inversion strategy involving centroid moment tensor inversion and kinematic finite-fault inversion is used to study the rupture history of the 2020 Oaxaca earthquake. The fault geometry and source duration time derived from the centroid moment tensor solution are used as prior information in linear kinematic finite-fault joint inversion. The finite-fault model shows rupture expanded bilaterally around the hypocenter, the peak slip is 3.5 m and the main slip was located at the depth of 15-30 km, the whole rupture lasted about 20 s, and a 95% moment rate was released at 15 s. The half duration of the finite-fault inversion is consistent with the centroid moment tensor inversion results (half duration 9 s), which shows the good resolution of the temporal information. The total scalar moment was 1.6 × 1020 Nm, equivalent to the moment magnitude of Mw 7.4. The integrated inversion strategy used in this study is useful since the prior information can be derived and used to constrain the rupture process. Both centroid moment tensor and finite-fault inversion mainly rely on identical temporal information provided by teleseismic P waveforms. The 2020 Oaxaca earthquake was mainly the interaction between Cocos and the North American plate, and the slow slip events may be the key factor affecting the seismogenic zone width in the Oaxaca region.